GENETIC ASPECTS OF CONGENITAL LONG QT SYNDROME - A. A. Chernova; S. Yu. Nikulina; A. V. Gul'bis (Столичная издательская компания, 2015)
The main symptoms and clinical types of long QT syndrome are described. Molecular genetic diagnostics and updated approaches to the management of patients with long QT syndrome are presented.